Modeling the Multiwavelength Emission of 3C 279 during the 14 yr Fermi-LAT Era - Krishna Mohana A; Alok C. Gupta; Junhui Fan; Narek Sahakyan; Claudia M. Raiteri; Lang Cui; Anne Lähteenmäki; Mark Gurwell; Merja Tornikoski; Massimo Villata (The Astrophysical Journal)
We report the results of our long-term multiwavelength spectral energy distribution (SED) study on the flat-spectrum radio quasar 3C 279 during the ∼14 yr (2008–2022) Fermi-Large Area Telescope (LAT) observing period. The Fermi-LAT data were complemented with data in other wave bands obtained from the Swift-X-Ray Telescope (XRT)/UVOT, the Whole Earth Blazar Telescope, along with other optical and radio data from several observatories. Different activity states were identified from the weekly binned γ -ray light curve, and it was possible to create 168 high-quality and quasi-simultaneous broadband SEDs. We modeled the SEDs using a one-zone leptonic scenario, including the emission region outside the broad-line region (BLR), involving synchrotron, synchrotron self-Compton, and external Compton mechanisms. Such extensive broadband modeling is essential for constraining the underlying multiwavelength radiative mechanisms in the 3C 279 jet and permits the estimation of the physical parameters and exploration of their evolution in time. Our SED modeling study suggests that the increase in the Doppler beaming factor, along with the variation of the emitting electrons, is the cause for the flares in this source. The multiwavelength emission of 3C 279 was found to be well explained by the scenario in which the emission region is outside the BLR at a distance of ∼6.42 × 10 ^3 R _S . However, for two of the very bright γ -ray states, the emission region was found to be close to the outer boundary of the BLR at a distance of ∼1.28 × 10 ^3 R _S from the central black hole.